1989
DOI: 10.1017/s0952523800004326
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y-Containing Neurons are Situated Predominantly Outside Cytochrome Oxidase Puffs in Macaque Visual Cortex

Abstract: Layers II/III of the primary visual cortex contain a regular pattern of histochemically detectable cytochrome oxidase (CO)-rich "puffs," which differ from the interpuff regions in their thalamo-cortical and cortico-cortical connectivity, receptive-field properties, and the density of inhibitory GABA-containing synaptic terminals. We used an immunocytochemical method, in combination with cytochrome oxidase histochemistry, to analyze the spatial relationship between neurons that contain neuropeptide Y (NPY) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…2). They had the morphological features of aspiny stellate neurons, which are characteristic of this region in normal adults (13,17). Although NPY-containing neurons were found in the blobs and in the interblob regions of the normal and enucleated animals, even cursory examination revealed that the majority of these neurons were situated in the interblob regions and very few were located in the blobs (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…2). They had the morphological features of aspiny stellate neurons, which are characteristic of this region in normal adults (13,17). Although NPY-containing neurons were found in the blobs and in the interblob regions of the normal and enucleated animals, even cursory examination revealed that the majority of these neurons were situated in the interblob regions and very few were located in the blobs (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The nearly flat shape of the opercular region allowed precise sectioning parallel to the pial surface at 40-gum intervals. Series of alternate sections were labeled histochemically for CytOx (6)(7)(8)(9)(10)(11)(12)(13) or for NPY-like immunoreactivity by the avidin/biotin/peroxidase method (16), as described previously (13,17).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations